Benefit of Six-minute Walk Test to the Quality of Life and Functional Capacity in Chronic Coronary Syndrome Patients - Poniton P. A. R. Simamora; Starry H. Rampengan; Agnes L. Panda (Universitas Sam Ratulangi, 2022)
Abstract: Patients with chronic coronary syndrome (CSS) have lower quality of life (QoL) due to the high frequency of angina and limits in carrying out activities, which is reflected in their low functional capacity. The six-minute walk test (6-MWT) is used to assess the patient's QoL and functional capabilities. This study aimed to determine the benefit of the 6-MWT on QoL and functional capacity in CCS. This was a literature review study using four databases, namely PubMed, ClinicalKey, Google Scholar, and Science Direct. The results obtained five studies discussing the utility of 6-MWT for risk stratification, three studies discussing the utility of 6-MWT in assessing functional capacity, and four studies discussing the utility of 6-MWT in assessing the QoL in CCS patients. The low functional capacity of CCS patients contributed to decreased QoL. In conclusion, the 6-MWT is a simple walking test that is easy to perform, valid, responsive and can be tolerated by CCS patients, and it can be used for risk stratification, functional capacity assessment, and QoL assessment.Keywords: six-minute walk test, chronic coronary syndrome, quality of life, functional capacityÂ Abstrak: Pasien sindrom koroner kronis (SKK) memiliki kualitas hidup yang lebih rendah karena tingginya frekuensi angina dan keterbatasan melakukan aktivitas yang tergambar dalam kapasitas fungsional yang rendah. Kualitas hidup pasien dan kapasitas fungsional dapat dievaluasi menggunakan tes latihan uji jalan enam menit (UJ6M). Penelitian ini bertujuan untuk mengetahui kegunaan UJ6M terhadap kualitas hidup dan kapasitas fungsional pada pasien SKK. Jenis penelitian ialah suatu literature review. Penelusuran data menggunakan PubMed, ClinicalKey, Google Scholar, and Science Direct. Hasil penelitian mendapatkan lima artikel membahas tentang kegunaan UJ6M untuk stratifikasi risiko, tiga artikel membahas tentang kegunaan UJ6M dalam menilai kapasitas fungsional, dan empat artikel membahas tentang kegunaan UJ6M dalam menilai kualitas hidup pasien SKK. Didapatkan bahwa kapasitas fungsional pasien SKK yang rendah memiliki kontribusi terhadap kualitas hidup yang menurun. Simpulan penelitian ini ialah uji jalan enam menit merupakan tes berjalan sederhana yang mudah dilakukan, valid, responsif serta dapat ditoleransi oleh pasien SKK yang berperan dalam stratifikasi risiko, penilaian kapasitas fungsional, dan kualitas hidup.Kata kunci: uji jalan enam menit; sindrom koroner kronis; kualitas hidup; kapasitas fungsional